Pelatihan dan Pendampingan Penyusunan Kebijakan dan Standar Pelayanan Publik pada Balai Teknik Air Minum - Eko Aristanto; Indri Damayanti; Zaenal Aripin (University of Merdeka Malang, 2021)
The implementation of this activity aims to improve the management of policy documents and service standards, increase the capacity of implementing resources and increase the value of public service performance at Balai Teknik Air Minum. Methods of implementing activities include socialization and field visits, desk documents, training and assistance related to public service policies and standards. The duration of the activity is 13 (thirteen) effective working days. Achievements in the implementation of these training and mentoring activities include: i) identified various weaknesses in improving the performance of public services that have been implemented, ii) increasing understanding of leaders and implementers of public services about managing policy documents and public service standards, iii) preparation of policy documents and public service standards which refers to the PANRB Ministerial Regulation No. 15/2014 and the PANRB Minister Regulation No. 17/2017, iv) The results of the self-assessment show an increase in the performance of public services from 2.66 (53.30) category C (Enough) to 3.45 (69.13) category B- (Good with Notes). The results of the evaluation of training and assistance activities in the preparation of policy governance documents and public service standards on 5 (five) indicators reached a score of 54 in the very good category.DOI: https://doi.org/10.26905/abdimas.v6i2.5465